Collaborative Governance: Potret Penyelenggaraan Ketenagakerjaan di Kabupaten Karawang - Prastio, Luki Oka; Indriyany, Ika Arinia (International Journal of Demos (IJD), 2024)
AbstractThis research is motivated by the high unemployment rate in Karawang Regency, which is higher than the national unemployment rate of 5%, dominated by the local workforce. This condition contradicts the image of Karawang Regency as the area with the most significant industrial area in Southeast Asia. This problem impacts the massive flow of urbanization into Karawang Regency and is exacerbated by discriminatory recruitment of the local workforce. This writing aims to analyze the current achievements of the collaborative governance of the Karawang Regency government together with APINDO (Indonesian Entrepreneurs Association), KADIN (Indonesian Chamber of Commerce), and the community in administering employment. This research uses the collaborative governance theory (Ansell & Gash, 2007), which focuses on Intermediate Outcomes. The results of the study show that the achievements of collaboration in organizing employment in Karawang Regency in the form of apprenticeships have not been able to reduce the high unemployment rate, improve community welfare, and provide guaranteed security for workers with low incomes below the district minimum wage, weak bargaining power of workers, and prone to violations in practice.Keywords: Â Collaborative Governance, National ApprenticeshipÂ AbstrakPenelitian ini dilatarbelakangi dari tingginya tingkat pengangguran di Kabupaten Karawang lebih tinggi di atas angka pengangguran nasional yang sebesar 5% didominasi oleh angkatan kerja lokal. Kondisi tersebut berkontradiktif dengan citra Kabupaten Karawang sebagai daerah dengan kawasan industri terbesar se-Asia Tenggara. Ihwal tersebut berdampak dari masifnya arus urbanisasi ke Kabupaten Karawang, dan diperparah dengan rekrutmen yang diskiminatif terhadap angkata kerja lokal Kabupaten Karawang. Tujuan penulisan ini adalah menganalisis capaian saat ini dari collaborative governance pemerintah Kabupaten Karawang bersama APINDO, KADIN, dan masyarakat dalam penyelenggaraan ketenagakerjaan. Penelitian ini menggunakan teori collaborative governance (Ansell & Gash, 2007) yang berfokus terhadap Intermediate Outcomes. Hasil penelitian menunjukkan capaian kolaborasi dalam penyelenggaraan ketenagakerjaan di Kabupaten Karawang dalam bentuk pemagangan belum dapat memangkas tingginya angka pengangguran, memperbaiki kesejahteraan masyarakat dan memberi kepastian jaminan bagi tenaga kerja dengan pendapatan yang rendah di bawah upah minimum kabupaten (UMK), lemahnya daya tawar pekerja, dan rawan pelanggaran dalam praktiknya.Kata kunci: Collaborative Governance, Pemagangan Nasional, Pengangguran